Legal Harmonization of Regional and National Development Plans for Sustainable Development Goals Implementation: Evidence from Bima Regency, Indonesia - Rahmah, Nuzulul; Firmanto, Taufik (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The legal harmonization between the Regional Medium-Term Development Plan (RPJMD) of Bima Regency and the National Medium-Term Development Plan (RPJMN) is a key prerequisite for achieving national development priorities and the Sustainable Development Goals (SDGs). However, SDG implementation at the regional level still faces challenges, indicating inconsistencies between regional and national planning frameworks. This study examines the extent to which harmonization between the RPJMD of Bima Regency and the RPJMN accommodates SDG principles and their implications for sustainable regional development. Using a normative juridical approach, the research analyzes statutory, conceptual, and policy documents related to development planning. The findings show varying levels of alignment in SDG integration. Strong harmonization is observed across basic services, poverty reduction, education, and health, while more complex targets, such as climate action, innovation, and institutional sustainability, remain only partially integrated. The study identifies regulatory frameworks, institutional capacity, political dynamics, and stakeholder participation as key factors influencing the effectiveness of harmonization. Although harmonization enhances policy coherence and supports the implementation of sustainable development, inconsistencies in legal and policy frameworks can hinder the comprehensive achievement of the SDGs at the regional level. Therefore, effective harmonization requires strengthened intergovernmental coordination, improved local institutional capacity, and broader stakeholder engagement to ensure integrated implementation of SDG targets.